Analisis Stabilitas Lereng dan Penanganan Longsoran Menggunakan Metode Elemen Hingga Plaxis V.8.2 (Studi Kasus : Ruas Jalan Liwa – Simpang Gunung Kemala STA.263+650) - Setyanto Setyanto; Ahmad Zakaria; Giwa Wibawa Permana (UNIVERSITAS LAMPUNG, 2016)
The downpour in most of Taman Nasional Bukit Barisan Selatan (TNBBS) Lampung areas caused landslide on a cliff in Liwa – Simpang Gunung Kemala STA.263+650 roadside so that a part of the roadside covered by the landslide. For this case, it takes slope stability analysis to determine safety factors of the slope in research site that can figuring accordance with the real conditions on the field in order to enable the approaches condition on the result of analysis and to simplify the process of figuring the handling, one of them is through the using of manual formulas and Plaxis program. The result of this research shows that soil parameters greatly affect the stability of slope. Partially saturated slope condition has the smallest stability compared to other conditions. Based on the analysis conducted before handling condition, it is acquired the deformed mesh = 885x10-3 m; ac- tive pore pressures = -168.89 m; effective stress = -535.76 kN / m2; safety factor = 0.2847. On the condition after handling, it is obtained values of deformed mesh = 818x10-3 m; active pore pres- sures = -132.36 m; effective stress = -209.77 kN / m2; safety factor = 1.3548.